2023
DOI: 10.3847/1538-4357/accbb8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Tornado Properties: A Substantial Contribution to the Solar Coronal Heating via Efficient Energy Transfer

Abstract: In solving the solar coronal heating problem, it is crucial to comprehend the mechanisms by which energy is conveyed from the photosphere to the corona. Recently, magnetic tornadoes, characterized as coherent, rotating magnetic-field structures extending from the photosphere to the corona, have drawn growing interest as a possible means of efficient energy transfer. Despite its acknowledged importance, the underlying physics of magnetic tornadoes remains elusive. In this study, we conduct a three-dimensional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 132 publications
2
9
0
Order By: Relevance
“…This indicates that observational estimates on the upflow of magnetic energy generated by photospheric motion might overestimate the energy that reaches the upper atmosphere. Our findings also reinforce the role of vortices as energy channels, as they breach these energy transport barriers, resulting in a significant augmentation of the magnetic energy availability in the presence of the vortices, around a three times higher Poynting flux than before, as quantified by Figures 9 and 10 and similarly obtained by Kuniyoshi et al (2023) for a magnetic tornado. After the vortices were established, the input of the magnetic energy into the upper atmosphere by the Poynting flux vortex was around 10 22 erg per second, which is the same amount of energy required by the nanoflare heating scenario (Pontin & Hornig 2020).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This indicates that observational estimates on the upflow of magnetic energy generated by photospheric motion might overestimate the energy that reaches the upper atmosphere. Our findings also reinforce the role of vortices as energy channels, as they breach these energy transport barriers, resulting in a significant augmentation of the magnetic energy availability in the presence of the vortices, around a three times higher Poynting flux than before, as quantified by Figures 9 and 10 and similarly obtained by Kuniyoshi et al (2023) for a magnetic tornado. After the vortices were established, the input of the magnetic energy into the upper atmosphere by the Poynting flux vortex was around 10 22 erg per second, which is the same amount of energy required by the nanoflare heating scenario (Pontin & Hornig 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Although previous studies (see, e.g., Wedemeyer-Böhm et al 2012;Yadav et al 2021;Kuniyoshi et al 2023) had already demonstrated the potential role of K-vortices for energy transport, our analysis has shown for the first time how the magnetic energy is flowing in the upper atmosphere and how the presence of vortices shapes the energy distribution. Our results strongly underline the effectiveness of magnetic energy mapping through FTLE in elucidating energy transport characteristics within the solar atmosphere.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We perform a two-dimensional numerical simulation that seamlessly covers the upper part of the solar convection zone and the corona. To this end, we use RAMENS 4 code (Iijima & Yokoyama 2015Iijima 2016;Wang et al 2021;Kuniyoshi et al 2023), in which we solve the compressible magnetohydrodynamic equations with gravity, radiation, and thermal conduction. The basic equations are given in the conservation form as follows…”
Section: Simulation Setupmentioning
confidence: 99%
“…Consequently, we adopt λ ⊥,* = 2000 km, slightly exceeding the typical granular scale (1000 km). The legitimacy of this presumption hinges on the wave generation mechanism; if Alfvén waves originate from intergranular-scale vortices (van Ballegooijen et al 2011;Finley et al 2022;Breu et al 2023;Kuniyoshi et al 2023), the scale of the intergranular lane should be designated as λ ⊥,* = 100-200 km (Berger & Title 2001;van Ballegooijen et al 2011). In future studies, the radial profile of λ ⊥ should be more accurately prescribed to align with observations (Abramenko et al 2013;Sharma & Morton 2023).…”
Section: Alfvén-wave Turbulencementioning
confidence: 99%